PENGARUH CUSTOMER EXPERIENCE DAN CUSTOMER SATISFACTION TERHADAP MINAT MENGGUNAKAN JASA SALON CLEOPATRA KOTA BENGKULU - Mutiara, Dwi Rahma; Arini, Eti (UM. Bengkulu, 2025)
Marketers must create an effective marketing strategy, that is, they need to first understand what business they are running because service or goods businesses are different businesses. The aim of the research is to determine the influence of customer experience on interest in using Cleopatra salon services in Bengkulu City. To determine the influence of customer satisfaction on interest in using Cleopatra salon services in Bengkulu City. To determine the influence of customer experience and customer satisfaction on interest in using Cleopatra salon services in Bengkulu City. This type of research is correlational, namely research to determine the influence and level of influence between two or more variables without any attempt to influence these variables. Customer experience (X1) has a positive and significant effect on interest in using services (Y) at Salon Cleopatra Bengkulu. Customer satisfaction (X2) influences interest in using services (Y) at Salon Cleopatra Bengkulu. Customer experience (X1) and customer satisfaction (X2) influence interest in using services (Y) at Salon Cleopatra Bengkulu. Keywords: Influence of customer experience, customer satisfaction